The Mediating Role of Organizational Commitment in the Relationship Between Transformational Leadership and Turnover Intention Among Generation Z - Puspasari, Erlin Nur; Diah Sofiah; Hetti Sari Ramadhani (Yayasan Minang Darussalam, 2025)
Human resources play a vital role in the sustainability of industries and organizations. As such, human resource management (HRM) is responsible for providing competent workforce, maintaining its quality, and managing labor costs efficiently. One of the key challenges faced by organizations today is the high turnover intention among employees particularly within Generation Z, which is known for having distinct characteristics and expectations compared to previous generations. This study aims to examine the influence of transformational leadership on turnover intention among Generation Z employees, with organizational commitment serving as a mediating variable. Data were collected through a survey involving 193 Generation Z employees working at Company ABC. The analysis was conducted using path analysis techniques. The results indicate a significant indirect effect of transformational leadership on turnover intention through organizational commitment, with a coefficient of -0.135. This suggests that transformational leadership can meaningfully reduce employees’ intention to leave, particularly when it fosters stronger commitment to the organization. Furthermore, the findings confirm that organizational commitment effectively mediates the relationship between transformational leadership and turnover intention. These insights offer valuable implications for organizational management in addressing turnover issues among Generation Z employees especially by cultivating a workplace environment that promotes transformational leadership development. Keywords: Turnover Intention, Kepemimpinan Transformasional, Organizational Commitment, Generasi Z